Pengetahuan Karyawan Akan Pentingnya Penggunaan Alat Pelindung Diri (Apd) Dalam Upaya Menjaga Kesehatan Dan Keselamatan Kerja (Studi pada PT. Iskandar Indah Printing Textile Surakarta Bagian Weaving) - Ardiansyah, Mochamad, Dr. Suwaji, M.Kes, dr. Hardjanto, M.S., Sp.OK (2015)
Basically, this research has done based on healthy and welfare when doing work. Every work place must be hold work healthy with caring increase, health increase (promotive) desease prevention (preventive), health recovery (rehabilitative) has implemented as comprehensive integrated and continuous until it can be realized the optimum public health degree. How application the knowledge at PT. Iskandar Indah Printing Textile employee will PPE very important in carrying health and welfare work was, and what kind of proponent and inhibiting factor to application PPE very important in carrying health and welfare work. In doing this research, the writer used descriptive research method with qualitative approach while in collecting the data, the writer used interview, observation, and documentation method, the data analysis used interactive model by Miles and Huberman The research product showed that the using of PPE in carrying health and welfare work at PT. Iskandar Indah Printing Textile Surakarta was exactly good, however, it needed more supervision again, so that no more ray infraction can make dangerous at their employees. So far this availability of facilities in PT. Iskandar Indah Printing Textile Surakarta was fulfilled from PPE to work, canteen, clinic, cleaning, guard doctore, nurse and etc. with existence all facilities was prepared by company to all their employees who helping the company in create the cloth with good quality and suitable in market. No wary effect that was gived by company to employees when they did infraction to PPE using at that time they worked which cause the employees habit become undicipline in using it and that has consequences will make dangerous their health and welfare at work.